A Bright Future for Precision Medicine: Advances in Fluorescent Chemical Probe Design and Their Clinical Application. Issue 1 (21st January 2016) - Garland, Megan; Yim, Joshua J.; Bogyo, Matthew
Abstract : The Precision Medicine Initiative aims to use advances in basic and clinical research to develop therapeutics that selectively target and kill cancer cells. Under the same doctrine of precision medicine, there is an equally important need to visualize these diseased cells to enable diagnosis, facilitate surgical resection, and monitor therapeutic response. Therefore, there is a great opportunity for chemists to develop chemically tractable probes that can image cancer in vivo. This review focuses on recent advances in the development of optical probes, as well as their current and future applications in the clinical management of cancer. The progress in probe development described here suggests that optical imaging is an important and rapidly developing field of study that encourages continued collaboration among chemists, biologists, and clinicians to further refine these tools for interventional surgical imaging, as well as for diagnostic and therapeutic applications. Highlights: Review of chemical probes for use in medical imaging applications Focus on chemically synthesized optical contrast agents Review of affinity- and activity-based targeted optical contrast agents Discussion of current challenges for translation of probes to clinical practice Abstract : Optical imaging is a rapidly developing field that encourages continued collaboration among chemists, biologists, and clinicians to develop optical chemical probes to image cancer in vivo. Garland et al. highlight recent advances in the development of optical probes and their applications for interventional surgical imaging.